Complex Systems Design & Management : Proceedings of the Ninth International Conference on Complex Systems Design & Management, CSD&M Paris 2018 /: Proceedings of the Ninth International Conference on Complex Systems Design & Management, CSD&M Paris 2018. ([2019]) - Unknown
No abstract available